The Chinese Television Industry - Keane, Michael (International screen industries, 2015)
"Though the television industry in China is enormous, fewer people are watching television screens. In this groundbreaking study, Michael Keene shows how television content is changing, how the Chinese government is responding to the challenges presented by digital media, and how businesses are brokering alliances in both traditional and new media sectors. Keane outlines the process of making content in China, focusing on regulatory institutions, ownership, censorship, programmes and channels, copygright, formats and the role of media bases. Spanning a wide variety of genres, the book examines four models of content internationalisation: licensing of programmes, formats, co-productions and online media. Written in an accessible style by one of the world's leading experts on China's media, this book explores how streamed online content is impacting on the state's control of ideas and management of the traditional broadcasting sector. This is the authoritative text for scholars, students, businesses and policy makers wanting to understand how the rapid evolution of Chinese media aligns with the nation's soft power initiatives"--Back cover.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé